The use of sorbitol-initiated polylactic acid as a coupling agent in resorbable phosphate glass fibre reinforced polylactic acid composites - Perera, Madhavie S. (2015)
Resorbable phosphate glass fibre (PGF) reinforced polymer composites have been investigated for use as fracture fixation plates. While demonstrating impressive initial properties, these composites have shown poor retention of mechanical properties after immersion in a hydrolytic environment. Existing commercially available coupling agents for conventional glass composites have been of limited value and so novel coupling agents have been created specifically for PGF/ Poly (lactide) composites. Previous work on sorbitol-initiated poly (lactide) (S-PLA) oligomers has shown potential both in single fibre and full body composites. This thesis investigates chain length and concentration optimisation of S-PLA based coupling agents on the interfacial properties of PGF reinforced composites, both as manufactured and throughout degradation.